The roles of communication process for an effective lean manufacturing implementation - Perumal Puvanasvaran; Hamdan Megat; Tang Sai Hong; Muhamad Mohd.Razali (Journal of Industrial Engineering and Management (JIEM), 2009)
Many companies are implementing lean manufacturing concept in order to remain competitive and sustainable, however, not many of them are successful in the process due to various reasons. Communication is an important aspect of lean process in order to successfully implement lean manufacturing. This paper determines the roles of communication process in ensuring a successful implementation of leanness in manufacturing companies. All the information of lean manufacturing practices and roles of communication in the implementation were compiled from related journals, books and websites. A study was conducted in an aerospace manufacturing in Malaysia. A five-point scale questionnaire is used as the study instrument. These questionnaires were distributed to 45 employees working in a kitting department and to 8 top management people. The results indicate that the degree of leanness were moderate.
Keywords: 650; leanness; communication process; aerospace company